Aspek Kearifan Lokal dalam Pelestarian Lingkungan - Husni Thamrin, M.Si (AL-FIKRA, 2017)
One of the ironiesof thedevelopment of human civilizationisthe developmentandmodernizationis intended toimprove the quality ofhuman life, butitis moreoftenthe presence ofpeoplebecome victims of development and modernization. More ironically, landandindigenous peoplesare victimsofan anthropocentricperspectiveand government policiesthat do notfavor thelocal community.This is attributable to several factors: First, the ideology of developmentalism does not incorporate local wisdom, especially regarding indigenous land policy and management and wealth preservation socio-economic-cultural as an integral part of all development programs. In the ideology of developmentalism traditionalism is the opposite of modernization so that all that is traditional, including indigenous lands rich culture and local wisdom considered adaptive in the times. Second, misperceptions people who think the indigenous people of Rokan Hilir as a destroyer of the environment that must be removed or relocated in order to save the environment. Yet, precisely Rokan Hilir indigenous peoples are the guardians of the environment from the invasion and destruction by outside communities, immigrant communities. Third, the nature only in terms of economic value, so that the release of the entire ecological value, the local political, social, cultural, spiritual and moral associated with customary land and the lives of indigenous peoples in the surrounding. Exploit indigenous lands and natural resources for the purpose of economic development and seen off as not have negative consequences for the existence of the indigenous population. Fourth, modernization and progress of civilization seen and measured primarily by the quality of the physical-economic-capitalistic. To improve thesocio-economiclevelof local communities, especiallythe Malaysmust bereturnedto theethical valuesof indigenous peoples. Socio-economicrights ofindigenous peoples should berecognized and guaranteedby the government. There must bepolitical commitmentatglobal and national levelstoprotectthe land rights ofindigenouspeoples andall the wisdomof socioeconomicThroughparadigm approacheco-culture istosave the existence ofindigenous landas a factorsupportingeconomic activityand allthe wealthandwisdom oftraditional, it can also besave theecological crisisis mainlycaused by faultyworldviewthatpolicy makersanthropocentric-capitalistic paradigmshould be changedtoeco-culture perspective.